Treatment of Refractory/High-Risk Pregnancies With Antiphospholipid Syndrome: A Systematic Review of the Literature - Hoxha, Ariela; Tormene, Daniela; Campello, Elena; Simioni, Paolo (Frontiers in Pharmacology, 2022)
Different treatment protocols have been employed to manage heparin/low dose aspirin refractory or high-risk pregnancies in antiphospholipid antibody syndrome (APS) pregnancies. A systematic review of the literature on additional treatments used in refractory and/or high-risk APS pregnancies was conducted. Records from February 2006 to October 2021were retrieved from Pubmed, Web of Science, Cochrane and the www.clinicaltrials.gov platform. Twenty-one studies met our eligibility criteria. Live birth rate is this study’s primary endpoint, while pregnancy complication and adverse events are secondary endpoints. Four-hundred-thirty-four pregnancies, 162 (37.3%) refractory and 272 (62.7%) high-risk/refractory pregnancies, were included. Both, IVIG < 2 gr/kg/monthly/HCQ/LDS and PEX/IA +/- LDS led to 100 % viable infants in refractory APS. Furthermore, HCQ 200-400 mg showed a higher live birth rate than HCQ + LDS (88.6% vs 82.7%). Following treatment protocol with HCQ 200-400 mg and IVIG < 2 gr/kg/monthly/HCQ/LDS, pregnancy complications rate of 16.7% and 83.3% were registered, respectively. Pravastatin 20 mg, IA weekly + IVIG 2 gr/monthly and PEX weekly + IVIg 2 gr/kg/monthly showed a higher live birth rate in high-risk APS pregnancies, respectively 100%, 100% and 92%. Whereas, the lower severe pregnancy complications were reported in pregnancies treated with PEX weekly + IVIg 2 gr/kg/monthly (11.1%). One (0.6%) case of dermatitis during treatment with HCQ was observed. The results of this study showed that HCQ 200-400 mg and PEX weekly + IVIG 2 gr/kg/monthly achieved a higher live birth rate in refractory APS and high-risk/refractory APS, respectively. The results presented provide clinicians with up-to date knowledge in the management of APS pregnancies according to risk stratification.